Analysis of The Decline in Votes for the Indonesian Democratic Party of Struggle (PDIP) in the 2024 Legislative Election in Salatiga City - M. Adnan Arsyad; Laila Kholid Alfirdaus; Rina Martini (Dinasti Research, 2025)
This study aims to analyze the causes of the decline in votes for the Partai Demokrasi Indonesia Perjuangan (PDIP) in the 2024 Legislative Election in Salatiga City. As a large party with a strong mass base in Central Java, especially Salatiga, the results of the 2024 legislative election showed a significant decline in support. This phenomenon is interesting to study further in order to understand the political, social, and cultural factors that influence changes in voter behavior. This study uses a qualitative approach with a descriptive-analytical method. Data collection techniques were carried out through in-depth interviews with members of the Salatiga City. Data is also strengthened through documentation and literature studies. The decline in PDIP votes in Salatiga City was influenced by several main factors. First, the political saturation of the community towards PDIP's dominance which was not accompanied by a renewal of communication and cadre strategies. Second, the weak role of local PDIP figures in responding to issues developing in the community, thus affecting the level of public trust in the party. Third, the entry of legislative candidates from other parties who were more adaptive and responsive to the needs of voters, especially among young people and marginal groups. In addition, the emergence of negative perceptions regarding transactional politics and the issue of political dowries also weakened PDIP's image in the eyes of the public. This study also found that the discontinuity between PDIP's national influence through the figure of President Joko Widodo and local dynamics in Salatiga was a weak point that was not optimally utilized by regional cadres. In this context, the party failed to carry out strong internal consolidation and build emotional relationships with voters in a sustainable manner. This study is expected to provide input for strengthening PDIP's political strategy, both structurally and culturally, as well as provide academic contributions to the study of voter behavior and local party dynamics in Indonesia.